2021
DOI: 10.2196/24162
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to Seek Mental Health Services During the COVID-19 Pandemic Among Chinese Pregnant Women With Probable Depression or Anxiety: Cross-sectional, Web-Based Survey Study

Abstract: Background Mental health problems are prevalent among pregnant women, and it is expected that their mental health will worsen during the COVID-19 pandemic. Furthermore, the underutilization of mental health services among pregnant women has been widely documented. Objective We aimed to identify factors that are associated with pregnant women’s intentions to seek mental health services. We specifically assessed pregnant women who were at risk of mental h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
1
12
2
Order By: Relevance
“…In terms of age and educational level as significantly predicted by our study, recent literature also suggests that education level, age, sex, and social condition had a significant association with knowledge about COVID-19 [41]. However, COVID-19-related lockdowns in participants' cities of residence, social support during the COVID-19 pandemic, and trust in health care providers were found to be protective factors of participants' intentions to seek help from mental health services, and this is consistent with our susceptibility score [42]. Similar to our findings, the more recent findings have also consistently confirmed strong associations between the pandemic and increased psychosomatic symptoms and negative emotions [43].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of age and educational level as significantly predicted by our study, recent literature also suggests that education level, age, sex, and social condition had a significant association with knowledge about COVID-19 [41]. However, COVID-19-related lockdowns in participants' cities of residence, social support during the COVID-19 pandemic, and trust in health care providers were found to be protective factors of participants' intentions to seek help from mental health services, and this is consistent with our susceptibility score [42]. Similar to our findings, the more recent findings have also consistently confirmed strong associations between the pandemic and increased psychosomatic symptoms and negative emotions [43].…”
Section: Discussionsupporting
confidence: 91%
“…In Australia, 40% of respondents would seek help from psychologists and 34% from psychiatrists ( 19 ), and the rate was 22.8 and 24.9%, respectively, in Hong Kong, China ( 20 ). Another survey in China among pregnant women with probable depression or anxiety during COVID-19 indicated that only 19% of the sample intended to seek professional help ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experiencing IPV and women’s economic dependency might also affect their care-seeking behavior in our study, which also corroborates with past literature [ 61 ]. Besides only a few women reported visiting professionals but with a disrupted therapeutic continuation due to low mental health literacy and a lack of understanding of psychosomatic symptoms [ 17 , 84 , 85 ]. Furthermore, our study found that women had limited access to quality mental health services, which is a significant factor in the higher mental health burden and treatment gap among women in Bangladesh [ 84 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides only a few women reported visiting professionals but with a disrupted therapeutic continuation due to low mental health literacy and a lack of understanding of psychosomatic symptoms [ 17 , 84 , 85 ]. Furthermore, our study found that women had limited access to quality mental health services, which is a significant factor in the higher mental health burden and treatment gap among women in Bangladesh [ 84 , 86 ]. This lack of professional mental health services in other developing countries are also caused by low mental health literacy, stigmatized attitudes, low affordability, and a workforce shortage [ 85 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%